The Analysis of the Effect of Leverage, Profitability and Executive Character on Tax Aggressiveness - Syaputra, Rio; Yurniwati, Yurniwati (E-Jurnal Akuntansi, 2022)
This study aims to examine the effect of leverage, profitability and executive character on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The sample selection technique used purposive sampling and obtained as many as 63 manufacturing companies listed on the Indonesia Stock Exchange. The data analysis technique used panel regression analysis using Eviews 10.0. Based on the results of hypothesis testing Leverage has no significant effect on tax aggressiveness. Profitability has a negative and significant effect on tax aggressiveness. Executive character has a positive and significant effect on tax aggressiveness. Leverage, Profitability and Executive Character together have a positive and significant effect on tax aggressiveness. Keywords: Tax Aggressiveness; Leverage; Profitability; Executive Character